Health Sciences Collection Development An Overview of Fundamental Knowledge and Practices - Gau, Karen H.; Kovar-Gough, Irene (Open textbook library., 2023)
This work was created by members of the Medical Library Association’s Collection Development Caucus to provide librarians with key concepts about health sciences collection development. The chapters provide an overview of the responsibilities and tasks involved in the development and management of health sciences collections; it is recommended that readers refer to the references and further reading sections in each chapter for a more detailed look at each topic. The first edition was published in 2019 and was updated with a second edition in 2023. This updated edition has a new section on unique collection genres; addresses Diversity, Equity, Inclusion and Accessibility in collections; incorporates significant updates to and expansion of previous content; and includes a glossary. New additions to each chapter, as applicable, include key communities and online courses for professional development.